Design Omnidirectional Movement Screw Blade of An Unmanned Mini Tiller - Sukmaji Cahyono; Ari Prasetyo (Mekanika: Majalah Ilmiah Mekanika, 2020)
Rotary tiller commonly used effectively to process the soil before planting in a terrain area. The design of the blade in rotary tiller was a significant factor in achieving soil breakup and more efficient inversion evenmore soil-fertilizer mixing. The blades design for an unmanned tiller with omnidirectional movement was required intensive research. A prototype unmanned tiller was manufactured, and it has four screw wheel blade that required optimal design and high accuracy movement for soil processing application.  In the present research, the design of the screw blade is investigated by mathematical and simulation method. The model was reverse engineering from commercial blades become screw-like blade wheel design. The calculation of the screw wheel design performance uses a mathematical approach identical to that of a screw conveyor and also it is supported by simulations to find the critical point of the structure and maximum defection in the screw wheel structure. Meanwhile, to study the lift-motion and moving of soil particles, simulations were carried out with variations in the depth of the screw blades on the ground surface, namely 20%, 40% and 50%. From the calculation result, the optimal rotational speed and power are found at the intersection point the percentage of soil depth and vortek efficiency, they are 350 rpm at 1.5 kW power.